Control de nivel implementado en la estación de entrenamiento gunt rt 450 del laboratorío de instrumentación industrial. - Gudiño P., Richard E. (2009)
The work that has been made, offers a general vision of the procedures that are involved in controlling an industrial process: Instrumentation (Electrical connections of sensors and actuators, and their conditioning), Data communication, and implementation of the controller. These are basically the three didactic aspects covered in GUNT RT 450 Modular Station. This station consists in a frame where you can implement a plant by mounting modular elements. A plant for level controlling has been chosen; in this plant the level of water that is in a tank is controlled by means of a valve which in turn manipulates the incoming flow. For this purpose three devices are being used: a PLC, an industrial controller, and Labview. For each one of these devices, a Labview interface has been developed in order to monitor the involved signals. Profibus and OPC specification are the technologies used for establishing the communication between the controllers and the PC. What has been achieved is to give the first step in the using of the equipment from the Industrial Instrumentation Laboratory